Hábitos alimentarios, estado nutricional y capacidad cognitiva de los alumnos del nivel Primaria De La I.E. 601023 Ex Petroleros - San Juan Bautista, 2024 - Rioja Curico, Iris Melissa (2024)
The presented research was to determine the eating habits, nutritional status, and cognitive capacity of primary level students from I.E. 6010231 Ex Petroleros - San Juan Bautista 2024. The study is quantitative, descriptive, non-experimental, correlational, and cross-sectional. The study population consisted of 116 students from 3rd to 6th grade of primary school. A food frequency questionnaire was used as the data collection instrument to evaluate eating patterns, nutritional status records, and an assessment questionnaire for cognitive ability (questionnaire on cognitive capacity). The results showed that 94.83% had a BMI/age with normal values, 3.45% were overweight, and 1.72% were obese. Regarding height, 94.83% were within the normal range for their age, while 5.17% had a low height. For hemoglobin, 72.41% had normal hemoglobin, 18.97% had mild anemia, and 8.62% had moderate anemia. In terms of eating habits, 56.90% of the population has a poorly healthy diet, 34.48% a healthy diet, and 8.62% an unhealthy diet. Regarding the students' cognitive capacity, 55.17% have regular cognitive capacity, 37.07% have good cognitive capacity, and 7.76% have poor cognitive capacity. A positive correlation coefficient was demonstrated, where a significant relationsip (p <0.05) between eating habits with BMI/Age, Height/Age, and also between eating habits and hemoglobin with cognitive capacity (p<0.01) of the students from I.E. 6010231 Ex Petroleros.